Challenges of novice teachers in Covid-19 at a rural school in Thabo Mofutsanyane district, South Africa - Refilwe Mofokeng (International Journal of Studies in Psychology)
This study explored the challenges faced by novice teachers during COVID-19 at a selected rural school in the Thabo Mofutsanyane District, Free State province of South Africa. It adopted the qualitative multiple case studies research method to analyse the problem statement comprehensively. Telephonic semi-structured interviews were held involving eight novice teachers (five females and three males) selected from two rural schools. Moreover, an Interpretive Phenomenological Analysis was used for data analysis. The results revealed novice teachers lacked psychological and emotional support services during COVID-19. They became vulnerable to the uncertainty of tomorrow, stress, depression, isolation, anxiety, the need to change to online learning abruptly, and the need to adapt to advanced technology. The results further found that Covid-19 and its related consequences will deteriorate as novice teachers become used to the new norm of doing things. Therefore, it is recommended that decision-makers and school managing bodies should support novice teachers by developing structural support strategies to help improve teacher well-being and mental health. Because without proper coping mechanisms, the negative feelings experienced by teachers could affect rural schools' teaching and learning processes.